2018
DOI: 10.1016/j.ijvsm.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid improves maturation rate and upregulates the expression of antioxidant-related genes inin vitromatured buffalo (Bubalus bubalis) oocytes

Abstract: Retinoic acid, vitamin A metabolite, plays a role in oocyte development and maturation in different ways including gene expression alteration and/or prohibiting oxidative stress. The objective of this study was to examine the effect of 9-cis-retinoic acid (9-cisRA) on the quality and maturation rate of buffalo oocytes. Cumulus-oocyte complexes (COCs, n = 460) were collected from ovaries of slaughtered buffalos. Varying concentrations of 9-cisRA (0, 5, 50, and 200 nM) were added to the maturation medium, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…Within the ovarian tissue, both CRBP and RBP are expressed in the granulosa and theca cells and control the movement of retinol from the blood to the growing ovarian follicles [10]. Levels of RBP and its substance retinol in the follicular fluid of large pre-ovulatory bovine ovarian follicles were found to be higher than in the atretic or smaller ovarian follicles [4].…”
Section: Forms Of Ramentioning
confidence: 99%
See 3 more Smart Citations
“…Within the ovarian tissue, both CRBP and RBP are expressed in the granulosa and theca cells and control the movement of retinol from the blood to the growing ovarian follicles [10]. Levels of RBP and its substance retinol in the follicular fluid of large pre-ovulatory bovine ovarian follicles were found to be higher than in the atretic or smaller ovarian follicles [4].…”
Section: Forms Of Ramentioning
confidence: 99%
“…In water buffaloes, Gad et al [4] found that supplementation with 5 nM of 9-cisRA to the in vitro maturation medium led to a higher oocyte maturation rate. Moreover, treatment with high levels of RA (50 and 200 nM) throughout the maturation stage revealed the minimum maturation (26.43%) and polar body rates (23.6%).…”
Section: Effects Of Ra and Retinol On Oocyte Until Blastocyst Formmentioning
confidence: 99%
See 2 more Smart Citations
“…The oocyte quality can be assessed by their ability to mature, fertilize and produce blastocyst (Hussein et al, 2006). Recently, the quality of oocytes and in vitro embryo production (IVEP) can be increased in river buffaloes by superstimulation of follicular activity by FSH followed by GnRH (Sakaguchi et al, 2019) or addition of Retinoic acid (vitamin A metabolite) to the media increased gene expression, maturation and decrease the ROS (Gad et al, 2018). The ovarian structures, morphology and CL are still requiring more investigation and study for improvement of oocyte quality and in vitro maturation in buffalo (Singh and Adams, 2000).…”
Section: Introductionmentioning
confidence: 99%